Mapping the patchwork: Exploring the subnational heterogeneity of child marriage in India. (December 2020) - McDougal, Lotus; Shakya, Holly; Dehingia, Nabamallika; Lapsansky, Charlotte; Conrad, David; Bhan, Nandita; Singh, Abhishek; McDougal, Topher L.; Raj, Anita
Abstract: Despite dramatic reductions in child marriage over the past decade, more than one in four girls in India still marry before reaching age 18. This practice is driven by a complex interplay of social and normative beliefs and values that are inadequately represented in national- or even state-level analyses of the drivers of child marriage. A geographic lens was employed to assess variations in child marriage prevalence across Indian districts, identify hot and cold spots, and quantify spatial dependence and heterogeneity in factors associated with district levels of child marriage. Data were derived from the 2015-16 National Family Health Survey and the 2011 India Census, and represent 636 districts in total. Analyses included global Moran's I, LISAs, spatial Durbin regression and geographically weighted regression. This study finds wide inter- and intra-state heterogeneity in levels of child marriage across India. District levels of child marriage were strongly influenced by geographic characteristics, and even more so by the geographic characteristics of neighboring districts. Districts with higher levels of female mobile phone access and newspaper use had lower levels of child marriage. These relationships, however, were all subject to substantial local spatial heterogeneity. The results indicate that characteristics of neighboring districts, as well as characteristics of a district itself, are important in explaining levels of child marriage, and that those relationships are not constant across India. Child marriage reduction programs that are targeted within specific administrative boundaries may thus be undermined by geographic delineations that do not necessarily reflect the independent and interdependent characteristics of the communities who live therein. The geographic, social and normative characteristics of local communities are key considerations in future child marriage programs and policies. Highlights: Child marriage prevalence is highly heterogeneous across Indian districts. Districts near state border districts tend to have higher levels of child marriage. Characteristics of districts and their neighbors influence child marriage. Geography affects the relationship between social normative factors and child marriage. Child marriage interventions may require joint action across states.